Evaluasi Layanan Gemilang Inovasi Daerah Pada Badan Perencanaan, Penelitian Dan Pengembangan Daerah Kabupaten Bintan - Putri Rachmadani; Shahril Budiman; Junriana Junriana; Raja Abumanshur Matridi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2026)
This study raises the title Evaluation of Gemilang Inovasi Daerah (Layangan Indah) Services at Badan Perencanaan, Penelitian dan Pengembangan Daerah Kabupaten Bintan. The purpose of this study was to determine the evaluation of consultation services regarding regional innovation through the Regional Innovation Gemilang Service (Layangan Indah) at Badan Perencanaan, Penelitian dan Pengembangan Daerah Kabupaten Bintan. This research refers to the operational concept put forward by Robert E. Stake in 1967, there are 2 stages in evaluating, namely in the planning and process aspects and evaluating the results aspects. The type of research used is descriptive with a qualitative approach, the location of this research is Badan Perencanaan, Penelitian dan Pengembangan Daerah Kabupaten Bintan. The research subjects and informants were employees of the Badan Perencanaan, Penelitian dan Pengembangan Daerah Kabupaten Bintan, regional innovation facilitator experts and users of Layangan Indah. Data collection techniques through observation, interviews, and documentation. The results of this study indicate that in the aspects of planning and process there is a mismatch of the Indah service implementation team, services through Zoom are not running effectively, there is no evaluation of Layangan Indah which has been running for three years. The suggestion given is that it is expected to optimize all existing human resources to carry out consultation services so that there is no accumulation of workload on one person.